Host and environmental factors associated with Hib in England, 1998–2002. Issue 8 (5th September 2007) - McVernon, J; Andrews, N; Slack, M; Moxon, R; Ramsay, M
Abstract : Background: Declining effectiveness of the UK's Hib vaccine programme was observed between 1998 and 2002. Objective: To provide insight into non-vaccine factors contributing to ongoing Hib disease in England after immunisation. Design: Postal questionnaire study, matched case–control design. Setting: Health Protection Agency Centre for Infections, England. Patients: Cases were children born after 1 January 1993 presenting with confirmed Hib infection in England between the start of 1998 and end of 2002, regardless of vaccination status. Controls were matched by date of birth and region. Main outcome measures: Odds ratios were calculated to assess the impact of host and environmental variables on disease risk. Results: Increased disease risk was noted among children with frequent antibiotic use (adjusted OR (AOR) (trend) 1.51 (95% CI 1.06 to 2.13); p = 0.02) and from sole-parent households (AOR 2.56 (95% CI 1.24 to 5.29); p = 0.01). These two risk factors were further related to each other, consistent with previously reported associations between infection and social deprivation. In fully immunised children, receipt of all three doses of the primary course as an acellular pertussis-containing combination vaccine (DTaP-Hib) increased the risk of vaccine failure (OR 2.88 (95% CI 0.99 to 8.37), p = 0.01). Day care attendance between 2 and 5 years of age was linked with a dose-dependent reduction in risk (AOR (trend) 0.79 (95% CI 0.66 to 0.93); p = 0.01), possibly because of natural boosting of immunity. Conclusions: The association noted between invasive infection and social deprivation in this and other studies is concerning and merits further investigation. The importance of ongoing surveillance of vaccine-preventable diseases to allow nested studies of this kind was reinforced.